Analysis of Factors Influencing Inpatient Satisfaction with Nutrition Services at RSKIA Sawojajar Bogor - Sari, RD Yunina Endang; Purnamawati, Dewi; Ernyasih, Ernyasih; Fajrini, Fini; Permatasari, Tria Astika Endah (International Journal Labs, 2025)
Patient satisfaction with hospital nutrition services is a crucial indicator of healthcare quality and recovery outcomes. Despite its importance, many hospitals still face challenges in meeting patient expectations regarding food quality and nutrition service delivery. This study aims to examine the factors affecting inpatient satisfaction with nutrition services. Using a descriptive-analytic method with a cross-sectional approach, the study involved 132 inpatients who met specific inclusion criteria. Data were collected through a structured questionnaire covering two main variables: patient perception of hospital food services and satisfaction with nutrition services, measured using a 4-point Likert scale. The results showed that most patients rated their perceptions and satisfaction positively, though some aspects received lower ratings from a small group of respondents. Statistical analysis revealed associations between satisfaction levels and demographic characteristics such as age, education, occupation, class of care, and length of stay, with varying levels of influence. Overall, food quality, service responsiveness, and personalized nutrition delivery emerged as key factors shaping patient satisfaction. This study provides valuable insights for improving nutrition service quality and promoting patient-centered care. Theoretically, it contributes to the understanding of healthcare service quality in nutrition services, while practically, it offers evidence-based recommendations for hospital management to enhance service delivery and patient care outcomes.